2003
DOI: 10.1190/1.1635055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of image gathers in factorized VTI media

Abstract: Because events in image gathers generated after prestack depth migration are sensitive to the velocity field, they are often used in migration velocity analysis for isotropic media. Here, we present an analytic and numerical study of P-wave image gathers in transversely isotropic media with a vertical symmetry axis (VTI) and establish the conditions for flattening such events and positioning them at the true reflector depth. Application of the weak-anisotropy approximation leads to concise expressions for refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Such a model was used by Slawinski et al (2004) to consider the traveltime inversion for the three parameters (a, b, and χ ) that define this model (as shown in equation 4 below). Moreover, factorized media can be used for modeling the subsurface (Sarkar and Tsvankin, 2003). An exhaustive study on factorized media is presented byČervený (1989).…”
Section: Introductionmentioning
confidence: 99%
“…Such a model was used by Slawinski et al (2004) to consider the traveltime inversion for the three parameters (a, b, and χ ) that define this model (as shown in equation 4 below). Moreover, factorized media can be used for modeling the subsurface (Sarkar and Tsvankin, 2003). An exhaustive study on factorized media is presented byČervený (1989).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, this is not the case, especially when well data are not available. Earlier studies showed that if only surface P-wave data are available, it will be difficult if not impossible to resolve accurately the three quantities V z , , and ␦ ͑Le Stunff et al, 2001;Sarkar and Tsvankin, 2004͒. When relying on surface data only, we suggest using the near offsets in the IMO domain to perform a standard isotropic interval-velocity analysis ͑such as depth residual moveout and tomography͒ prior to the estimation of and ␦.…”
Section: Wrong V Zmentioning
confidence: 98%
“…Application of isotropic prestack depth imaging in regions with significant anisotropy will result in poor image quality and wrong positioning of subsurface reflectors ͑Alkhalifah and Larner, 1994; Alkhalifah, 1997;Sarkar and Tsvankin, 2003͒. Two of the most common problems are ͑1͒ inaccurate imaging of steeply dipping reflectors and ͑2͒ less than optimal isotropic prestack depth migration ͑PSDM͒ results that do not tie wells.…”
Section: Introductionmentioning
confidence: 96%
“…The factorized model (Sarkar and Tsvankin, 2003;Stovas, 2010) involves anisotropy and vertical heterogeneity. In our case, the factorized medium is defined as a transversely isotropic model with a vertical symmetry axis (VTI) under the acoustic approximation (Alkhalifah, 1998).…”
Section: Diving Waves In a Factorized Vti Mediummentioning
confidence: 99%
“…The factorized model, assuming vertical heterogeneity and constant anisotropy parameters, is useful in seismic data processing and modeling (Alkhalifah, 1995;Sarkar and Tsvankin, 2003). The raytracing problem in factorized models with elliptic anisotropy is discussed extensively by Rogister and Slawinski (2005).…”
Section: Introductionmentioning
confidence: 99%